The Criminal Act of Desertion Against TNI Members Reviewed from Influencer Background and Prevention Efforts - Pasaribu, Roy Leonard Hosea; Widijowati, Rr. Dijan (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
Discipline is a fundamental principle in the military, especially for soldiers of the Indonesian National Armed Forces (TNI). Serious disciplinary violations such as desertion, the act of leaving duty without permission, remain a major problem within the TNI. This study aims to analyze in-depth the application of the law to the crime of desertion within the TNI, as well as the factors that influence it, and examine effective preventive measures to reduce the number of desertions in the Indonesian Navy (AL). This study uses a normative legal research method. Data were collected through a literature review focusing on laws, government regulations, and related decisions. Data analysis was conducted descriptively and analytically. The application of the law to desertion is strictly regulated in Articles 87 and 89 of the Military Criminal Code (KUHPM), which stipulate sanctions ranging from imprisonment to dismissal. The government must focus more on proactive prevention through a comprehensive approach, including improving soldier welfare, strengthening mental and psychological development, improving leadership and supervision, and optimizing recruitment and legal education.